Bank Efficiency Research of Chinese Commercial Banks based on Data Envelopment Analysis - FENG, JIERUI (2012)
According to the related agreements accepted by China on accessing World Trade Organization, it has become reality for foreign banks to enter domestic financial markets. The diversity of financial markets and trades will make Chinese banking industry face greater challenges on the aspects of talents, operations, techniques and management. In addition, risk factors will become more complicated, such as market risks, operational risks and credit risks. Therefore, facing this new challenging situation, Chinese banking industry needs to learn to improve the ability of gaining profits and the level of efficiency through constantly perfecting their own corporate governance mechanism without the complete paternal care of Chinese government. Consequently, the research of commercial banks’ efficiency in China draws great attention in both theoretical and practical circles. Nevertheless, comparing to foreign similar efficiency researches, there are certain shortages of the theories and methods used in Chinese banking industry. So, this dissertation seeks to improve the existing efficiency researches while investigating the internal relationship between bank efficiency and structural determinants of banking industry in China. By doing so, it can be helpful to support feasibility of some Chinese banking innovations, as well as perfecting current theoretical systems. Key words: Bank Efficiency; DEA; State-owned; Joint-equity; Efficiency Determinants